Frequent Manipulation of Resistance Training Variables Promotes Myofibrillar Spacing Changes in Resistance-Trained Individuals - Fox, Carlton D.; Mesquita, Paulo H. C.; Godwin, Joshua S.; Angleri, Vitor; Damas, Felipe; Ruple, Bradley A.; Sexton, Casey L.; Brown, Michael D.; Kavazis, Andreas N.; Young, Kaelin C.; Ugrinowitsch, Carlos; Libardi, Cleiton A.; et al. (Frontiers in Physiology, 2021)
We sought to determine if manipulating resistance training (RT) variables differentially altered the expression of select sarcoplasmic and myofibril proteins as well as myofibrillar spacing in myofibers. Resistance-trained men (n = 20; 26 ± 3 years old) trained for 8 weeks where a randomized leg performed either a standard (CON) or variable RT protocol (VAR: manipulation of load, volume, muscle action, and rest intervals at each RT session). A pre-training (PRE) vastus lateralis biopsy was obtained from a randomized single leg, and biopsies were obtained from both legs 96 h following the last training bout. The sarcoplasmic protein pool was assayed for proteins involved in energy metabolism, and the myofibril protein pool was assayed for relative myosin heavy chain (MHC) and actin protein abundances. Sections were also histologically analyzed to obtain myofibril spacing characteristics. VAR resulted in ~12% greater volume load (VL) compared to CON (p < 0.001). The mean fiber cross-sectional area increased following both RT protocols [CON: 14.6% (775.5 μm2), p = 0.006; VAR: 13.9% (743.2 μm2), p = 0.01 vs. PRE for both], but without significant differences between protocols (p = 0.79). Neither RT protocol affected a majority of assayed proteins related to energy metabolism, but both training protocols increased hexokinase 2 protein levels and decreased a mitochondrial beta-oxidation marker (VLCAD protein; p < 0.05). Citrate synthase activity levels increased with CON RT (p < 0.05), but not VAR RT. The relative abundance of MHC (summed isoforms) decreased with both training protocols (p < 0.05). However, the relative abundance of actin protein (summed isoforms) decreased with VAR only (13.5 and 9.0%, respectively; p < 0.05). A decrease in percent area occupied by myofibrils was observed from PRE to VAR (−4.87%; p = 0.048), but not for the CON (4.53%; p = 0.979). In contrast, there was an increase in percent area occupied by non-contractile space from PRE to VAR (10.14%; p = 0.048), but not PRE to CON (0.72%; p = 0.979). In conclusion, while both RT protocols increased muscle fiber hypertrophy, a higher volume-load where RT variables were frequently manipulated increased non-contractile spacing in resistance-trained individuals.